2021
DOI: 10.1021/jacs.1c09827
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Stitching Polymerization of Alkynylsilylacetylenes

Abstract: Polymers possessing a silicon-bridged π-conjugated repeating unit constitute an important class of compounds for their potential utility as optoelectronic materials. Herein we developed a rhodium-catalyzed stitching polymerization of nonconjugated and readily prepared alkynylsilylacetylenes for the synthesis of new πconjugated polymers with ladder-type silicon-bridged repeating units. The polymerization proceeded smoothly by employing a Rh/ tfb complex as the catalyst, and not only diynes but also triynes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…In particular, polymerization in the presence of a combination of [RhCl(tfb)] 2 and Et 3 N in THF at –10 °C gave poly-25a ( M n = 84000) in a nearly quantitative yield (Scheme 16 ). 24 Various monomers having different substituents on the alkyne could be used to give the corresponding stitched polymers with M n values of 23000–46000 (Scheme 16 ). In addition, by introducing appropriate substituents on the silicon atoms, the solubility of the polymers toward regular organic solvents, diluted acidic water, or fluorous solvents could be controlled without changing the π-conjugation structures in the main chain.…”
Section: Synthesis Of New π-Conjugated Polymers By Stitching Polymeri...mentioning
confidence: 99%
“…In particular, polymerization in the presence of a combination of [RhCl(tfb)] 2 and Et 3 N in THF at –10 °C gave poly-25a ( M n = 84000) in a nearly quantitative yield (Scheme 16 ). 24 Various monomers having different substituents on the alkyne could be used to give the corresponding stitched polymers with M n values of 23000–46000 (Scheme 16 ). In addition, by introducing appropriate substituents on the silicon atoms, the solubility of the polymers toward regular organic solvents, diluted acidic water, or fluorous solvents could be controlled without changing the π-conjugation structures in the main chain.…”
Section: Synthesis Of New π-Conjugated Polymers By Stitching Polymeri...mentioning
confidence: 99%
“…[7,8] Nonetheless, this strategy is limited to thiophene [9] -and phenylene [10] -based arene monomers, and few reports have addressed the synthesis of polyacetylene (PA) from alkyne monomers. [11,12] In 2019, Shintani et al reported pioneering works on a novel strategy for Rh-catalyzed stitching polymerization to synthesize conjugated polymers containing a fused bicyclic ring from non-conjugated 1-aryl-1,5hexadiyne monomers. [11] However, the synthetic method showed broad dispersity, and despite the formation of a rigid bridged conjugated structure during polymerization, the effective conjugation length was somewhat shorter than the previous PAs containing the ring in the backbone, thereby increasing the optical band gap to 2.02 eV (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Starting with poly(isothianaphthene) [6] first reported in 1984, various fused ring systems have been introduced to semiconducting materials and widely used in polymer electronics [7, 8] . Nonetheless, this strategy is limited to thiophene [9] ‐ and phenylene [10] ‐based arene monomers, and few reports have addressed the synthesis of polyacetylene (PA) from alkyne monomers [11, 12] . In 2019, Shintani et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we recently developed a rhodium-catalyzed stitching polymerization as a new method to synthesize π-conjugated polymers possessing a ladder-type repeating unit (Scheme a) . In this polymerization, readily accessible non-conjugated oligo­(alkyne)­s were used as monomers, and construction of bridged π-conjugated repeating units and chain propagation were achieved at the same time through inter- and intramolecular multiple alkyne insertion processes under rhodium catalysis.…”
Section: Introductionmentioning
confidence: 99%